Formation of Tolerance Character Through Learning Pancasila in Grade IV SDN 164 Pekanbaru - Wini Ihwana; Nadilla Resti Amanda; Asmardi Asmardi; Zulhidah Zulhidah (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to describe the strengthening of the value of tolerance through learning Pancasila Education in grade IV students of SDN 164 Pekanbaru. The background of this research is based on the behavior of students who still do not appreciate differences in religion, ethnicity, culture, and peer background, so a learning strategy is needed that is able to foster a tolerant attitude from an early age. The method used in this study is library research, by collecting data and information from various sources such as books, journals, scientific articles, theses, and other relevant references. The collected data was analyzed descriptively to explain facts related to the application of tolerance values in Pancasila Education learning and explain relevant character strengthening strategies. The results of the study show that instilling the value of tolerance through learning Pancasila Education can form an attitude of respecting differences, accepting the opinions of friends, and working together in group activities regardless of individual background. The cultivation of tolerance values is carried out through a combination of theoretical learning methods, hands-on practice, critical thinking skill development, and teacher examples. Despite this, some students still exhibit exclusive behaviors and minor conflicts caused by a lack of understanding of differences, so strengthening the value of tolerance needs to be done consistently and sustainably. This study recommends the integration of tolerance values in every learning activity, strengthening teacher examples, and parental involvement in guiding students to implement tolerant attitudes at home. Thus, learning Pancasila Education is an effective means to form tolerant character, increase social awareness, and prepare students to be able to live harmoniously in a multicultural society.